Pemanfaatan Media Infokus pada Pembelajaran PAI Untuk Meningkatkan Hasil Belajar di SMPN 2 Ampek Angkek - Mulya, Vivi Mavika; Trisno, Bambang; Jowaldi, Jowaldi (Indonesian Research Journal on Education, 2023)
Learning media is a tool that can help the teaching and learning process so that the meaning of the message conveyed becomes clearer and the goals of education or learning can be achieved effectively and efficiently. Learning outcomes are results given to students in the form of assessments after participating in the learning process by assessing knowledge, attitudes, and skills in students with changes in behavior. Learning media functions as a learning resource for students to obtain messages and information provided by the teacher so that learning materials can be further enhanced and form knowledge for students. Learning media can improve student learning outcomes with learning media: the teaching and learning process becomes easy and interesting so that students can understand and understand lessons easily, student learning efficiency can increase because it is under learning objectives, and helps students concentrate on learning because learning media is interesting and under the needs of students, increase student motivation because students' attention to lessons can increase, provide a thorough experience in learning so that students can understand clearly from the material provided better understand the material as a whole, students are involved in the learning process so that students actively follow and are involved in the process learning and students have the opportunity to be creative and develop their potential.